1984
DOI: 10.1029/ja089ia03p01683
|View full text |Cite
|
Sign up to set email alerts
|

F layer ionization patches in the polar cap

Abstract: Ground‐based optical and digital ionosonde measurements were conducted at Thule, Greenland to measure ionospheric structure and dynamics in the nighttime polar cap F layer. These observations showed the existence of large‐scale (800–1000 km) plasma patches drifting in the antisunward direction during a moderately disturbed (Kp ≥ 4) period. Simultaneous Dynamics Explorer (DE‐B) low‐altitude plasma instrument (LAPI) measurements show that these patches with peak densities of ∼106 el cm−3 are not locally produced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
304
3

Year Published

1992
1992
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 327 publications
(321 citation statements)
references
References 25 publications
8
304
3
Order By: Relevance
“…These structures may form from processes such as particle precipitation on the nightside [e.g., Noël et al, 2000Noël et al, , 2005Sofko et al, 2007] and photoionization creating polar cap patches on the dayside [Weber et al, 1984]. Other structures which may provide locations for HF coherent radar scatter are the midlatitude trough [Moffett and Quegan, 1983] and traveling ionospheric disturbances (TIDs) [e.g., Pryse et al, 1995].…”
Section: Comparisons To Irimentioning
confidence: 99%
“…These structures may form from processes such as particle precipitation on the nightside [e.g., Noël et al, 2000Noël et al, , 2005Sofko et al, 2007] and photoionization creating polar cap patches on the dayside [Weber et al, 1984]. Other structures which may provide locations for HF coherent radar scatter are the midlatitude trough [Moffett and Quegan, 1983] and traveling ionospheric disturbances (TIDs) [e.g., Pryse et al, 1995].…”
Section: Comparisons To Irimentioning
confidence: 99%
“…Observations [Weber et al, 1986;Basu et al, 1994] as well as (large-scale) modeling [Sojka et al, 1993] show that the patches convect to distances of the order of 3000 km [Weber et al, 1986] and for periods of a few hours while retaining their integrity. The mesoscale irregularities, observed within these patches throughout the polar cap region [Weber et al, 1984[Weber et al, , 1986Tsunoda, 1988;Basu et al, 1990Basu et al, , 1995, occasionally are more intense on the trailing edge than on the leading edge [Weber et al, 1984].…”
Section: Introductionmentioning
confidence: 99%
“…The largescale structures ranging from hundreds to thousands of kilometers have been categorized as "patches" (in the polar cap) or "blobs" (at auroral latitudes) [Weber et al, 1984[Weber et al, , 1986Basu et al, 1990Basu et al, , 1994. The mesoscale features in the range of 0.1 km to tens of kilometers are believed to arise from naturally occurring instabilities in a two-component plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Particle precipitation has also been cited as a possible source of patch plasma. Weber et al (1984) suggested that, if the¯ux-tube convected Sunward along the cusp for tens of minutes before turning anti-Sunward into the polar cap, then there might be su cient time for build-up of ionisation. Modelling studies by Sojka and Schunk (1986) indicated that densities might increase by a factor of two above background within a¯ux tube that convected through cusp-precipitation for some 10±15 min.…”
Section: Introductionmentioning
confidence: 99%